Evaluation of Drainage Channel on Meteorological Road, Laut Dendang Village, Deli Serdang Regency - Fikri Damara; Desi Paskalia Tinambunan; Sakkot Matua Gong Hasibuan; Rachmat Mulyana; Meuthia Fadila; Ahmad Zulfikar; Wisnu Prayogo; I Wayan Koko Suryawan; M. Faisi Ikhwali; Iva Yenis Septiariva; Nur Novilina Arifianingsih; Sapta Suhardono; Annisa Fillaeli (Journal of Sustainable Infrastructure, 2022)
Drainage is one way of removing unwanted excess water in an area and dealing with the effects of excess water in the system. When the rainy season comes, there are almost floods or puddles on urban roads. The large population also makes the volume of drainage channels fill up quickly, while the drainage capacity tends to decrease due to rainwater (erosion) and sedimentation. Meteorological Street, Laut Dendang Village, Percut Sei Tuan sub-district, Deli Serdang Regency, is one of the villages that is frequently flooded every time it rains. On these issues, the researcher highlights the importance of evaluating the Deli Serdang Regency's drainage system along Meteorological Road to anticipate when the rainy season comes. The general exponential method can determine whether the existing drainage volume can still accommodate terrestrial run-off and domestic wastewater in the next 30 years and calculate the population growth. Based on the research results from rainfall data obtained from Meteorology Road, the rainfall intensity value for the last ten years (2010 - 2019) was 10.538 mm/day. Thus, the amount of discharge flowing in the drainage channel (Qplansning) is equal to 0.832 m3/sec, while the planned Q for the next ten years is 0.874 m3/sec, for the next 20 years is 0.953 m3/sec, and 30 years into the future. front is 1.111 m3/sec. Based on the calculation results, Qplans exceeds Qeksisting. Therefore, a new channel plan is needed.